Implementasi Program Indonesia Pintar (PIP) Tingkat Sekolah Menengah Atas di Kota Tanjungpinang Tahun 2023 : studi di SMAN 4 Tanjungpinang - Nadia Nadia; Fitri Kurnianingsih; Ramadhani Setiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out how the implementation of the Smart Indonesia Program (PIP) in Tanjungpinang city in 2023 stueis at SMAN 4 Tanjungpinang, using descriptive method of qualitative approach, data collection is done by observation, interviews, documentation, and recording secondary data related to research problems, then qualitative alaysis is carried out. The results showed that implementation of the Smart Indonesia Program (PIP) in Tanjungpinang city in 2023 study at SMAN 4 Tanjungpinang has been well implemented although there are several variabels that must be improved in the implementation of PIP in the future. Such as the lack of dissemination on information about PIP, there is no additional quita given, and the lack of use of funds obtained by recipitiens so that yhis can result in misuseof funds. Therefore, it is hoped that in the future the government can overcome the shortcomings in the implementation of PIP so that the implementationcan be more effective and efficient.